Extra mammary Paget's disease of the vulva - Debabrata Barmon; Amal Chandra Kataki; Lima Imchen; Jagannath Dev Sharma (Wolters Kluwer Medknow Publications, 2012)
Extra mammary Paget's disease (EMPD) is a rare condition, which affects postmenopausal women. Wide local excision may not be appropriate in elderly patients with extensive disease. It is an uncommon malignant neoplasia with a high local recurrence rate. The standard treatment is local excision of the affected area with adequate margins; however, 40~45% of cases recur after surgery within 4 years. Although surgery is currently considered the preferred primary treatment for EMPD, it has a high relapse rate due to the multifocal nature of the disease. Hence, RT in selected cases of EMPD of vulva may be beneficial.